Ventricular tachycardia induced by a backup pacing stimulus in a patient with a dual chamber pacemaker with AutoCapture. Issue 6 (25th February 2021) - Greenspon, Arnold J.; Frisch, Daniel R.; Ho, Reginald T.; Pavri, Behzad B.
Abstract: Manufacturers of cardiac implantable electronic devices have incorporated automatic features to allow for remote monitoring, improve device longevity, and additional safety. Algorithms to automatically measure capture threshold and adjust output to preserve battery life are one such feature. Automatic features may occasionally result in unexpected or undesirable clinical outcomes. We report on a patient who developed ventricular tachycardia inadvertently induced by the AutoCapture. feature of an Abbott/St. Jude Medical (SJM) pacemaker.